NATIONAL CYBERSECURITY POLICY IN THE U.S AND INDONESIA - Anang Setiyawan (UNTAG Law Review, 2019)
Cyber attacks are a dangerous threat to a country that has a high dependence on communication and information technology. Cyber attacks can be used systematically to disrupt and dysfunction an infrastructure and network so that it can cause not only physical damage but also fatalities. Cyber attacks are complex and multidomain; consequently, they require comprehensive and targeted policies. Indonesia in the early stages of developing cyber policies, therefore it can learn from America in developing policies in dealing with cyber threats.